2012
DOI: 10.1007/s11523-012-0211-3
|View full text |Cite
|
Sign up to set email alerts
|

Recent successes of cancer immunotherapy: a new dimension in personalized medicine?

Abstract: Until recently, cancer therapy was limited to "debulking approaches" including surgery, chemo-radio-and hormono-therapy and compounds targeting oncogenes or proangiogenic pathways. Unfortunately, phase III studies pointed out that such strategies, remarkable against primary tumors, mostly affected time to progression but rarely overall survival, suggesting that long-term protective effects were not achieved. Immunotherapy which has long been opposed to chemotherapy because of its susceptibility to drug-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The immunogenicity of cell death can significantly influence subsequent antitumor immune response and the overall efficacy of a drug. [21][22][23] Specifically, it has been suggested that the translocation of the endoplasmic reticulum resident calreticulin-ERp57 complex to the plasma membrane is useful for immunogenic cell death. 24 Subsequently, it was shown that the nuclear alarmin HMGB1 has to be released into the tumor microenvironment to engage TLR4 on host DCs to facilitate antigen processing and presentation.…”
Section: Introductionmentioning
confidence: 99%
“…The immunogenicity of cell death can significantly influence subsequent antitumor immune response and the overall efficacy of a drug. [21][22][23] Specifically, it has been suggested that the translocation of the endoplasmic reticulum resident calreticulin-ERp57 complex to the plasma membrane is useful for immunogenic cell death. 24 Subsequently, it was shown that the nuclear alarmin HMGB1 has to be released into the tumor microenvironment to engage TLR4 on host DCs to facilitate antigen processing and presentation.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence that the immune system of the host can influence cancer incidence, cancer growth, response to therapy, and the prognosis of the disease, is growing [18]. Therefore it was thought that conventional therapy combined with immunotherapy based on a pretreatment profile of the immune system of the host could be a valuable tool to increase the survival of early stage NSCLC [19].…”
Section: Discussionmentioning
confidence: 99%
“…Several complementary treatment regimes such as immune cell transfer (adoptive immunotherapy), tumour vaccines, cytokine therapy, and monoclonal antibodies targeting immune response checkpoints [1][3] may form part of this therapy. One form of adoptive immunotherapy for cancer patients involves loading tumour-associated antigens (TAAs) in vitro onto macrocytic dendritic cell (DCs) precursors isolated from the patient.…”
Section: Introductionmentioning
confidence: 99%